Faktor -Faktor Tekanan Kerja Yang Mempengaruhi Keseimbangan Kehidupan Kerja Dalam Kalangan Jururawat - Aisha, Nur Fadzlin; Ruslan, Rumaizah (Research in Management of Technology and Business, 2020)
Work stress is a psychosocial hazard and it has becoming a current global phenomenon. This study was conducted to identify the factors of work stress and to determine the relationship between work stress factors on work life balance among hospitals’ nurses around Johor. This study used quantitative method using questionnaire where an online survey through Google Form was employed. There were 80 complete forms returned and analysed by using the IBM Statistical Package for The Social Science (SPSS) version 25.0 software. The results showed that there was a significant correlation between the factors of work stress on work life balance among nurses. The interpersonal relationship factor in the workplace is the highest factor contributing to the work stress among nurses (r= 0.409, p<0.001). While the second highest factor is the workload (r=0.346, p=0.002) and is followed by organizational structure and climate and role conflicts (r=0.346, p=0.002 and r=0.316, p=0.004, respectively). Following the findings, appropriate courses and training especially on work stress management skills, could be recommended to the management as an effort in lower the risk of work stress among nurses.